Development and validation of a radiologically-based nomogram for preoperative prediction of difficult laparoscopic cholecystectomy - Zhu, Bo; Wang, Yingxin; Zhang, Zhenduo; Wang, Liwei; Ma, Yashuai; Li, Ming (Frontiers in Medicine, 2025)
BackgroundPreoperative prediction of difficult laparoscopic cholecystectomy (DLC) remains challenging, as intraoperative anatomical complexity significantly increases complication risks. Current studies have not reached consensus on definitive risk factors for DLC.Materials and methodsThis retrospective study aimed to identify DLC risk factors and develop a predictive model. We analyzed clinical data from 265 patients undergoing laparoscopic cholecystectomy (LC) at the Department of General Surgery, Shijiazhuang People’s Hospital, between September 2022 and June 2024. Risk factors were explored through least absolute shrinkage and selection operator (LASSO) regression, multivariate analysis, and receiver operating characteristic (ROC) curves, with a nomogram constructed for prediction.ResultsAmong 265 eligible patients, four independent risk factors were identified: thickness of gallbladder wall (p = 0.0007), cystic duct length (p < 0.0001), cystic duct diameter (p < 0.0001), and gallbladder neck stones (p = 0.0002). The nomogram demonstrated strong predictive performance, with an area under the curve (AUC) of 0.915 in the training cohort and 0.842 in the validation cohort. Calibration curves indicated excellent model fit.Conclusion and discussionThe proposed predictive model integrating gallbladder neck stones, thickness of gallbladder wall, cystic duct length, and cystic duct diameter may assist surgeons in preoperative DLC risk stratification. Further validation through multicenter prospective studies is warranted.